SODIUM GLUCOSE COTRANSPORTER-2 INHIBITOR TOLERABILITY AND RENAL SAFETY DURING RAMADAN FASTING - G, Kian Guan; S, Saiful Shahrizal; Z, Miza Hiryanti (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION During Ramadan, typically Muslims fast for 14 hours a day. For persons with diabetes, taking sodium glucose cotransporter-2 inhibitors may induce polyuria and dehydration leading to acute kidney injury. This study looked into the tolerability and renal function of persons with diabetes starting SGLT2 inhibitors during Ramadan fasting. METHODOLOGY This is a prospective cohort, interventional study conducted during April and May 2019. Muslim subjects with diabetes who were willing to fast during Ramadan were recruited from diabetic clinic Hospital Tengku Ampuan Afzan. Baseline blood and anthropometry measurements were taken. They were given Empagliflozin 25 mg OD starting 2 weeks prior to Ramadan and continued throughout fasting. During the 2nd visit between 2nd to 4th week of Ramadan, patients had their blood testing and interview via questionnaire. Visit 3 was done 1-month post visit 2. RESULT Thirty-four subjects were recruited. 2 subjects subsequently withdrew. Mean duration of diabetes was 9.8 years and HbA1c was 10.08%. 41.3% of subjects reported thirst after starting the drug whilst 42.4 % experienced polyuria. 31% had hunger sensation but only 1 subject had documented hypoglycaemia. 17.2% of subjects need to take breakfast earlier. None reported UTI symptoms. Mean delta urea was -0.78 mmol/L and mean delta creatinine -7.2 umol/L. 25% had changes of creatinine above 20%. One subject was withdrawn as her serum creatinine doubled after commencing treatment. Her prior medicine included multiple diuretics (frusemide, hydrochlorothiazide and spironolactone). However, subject denied uraemic symptoms and renal function improved once study drug was stopped. CONCLUSION Dehydration and polyuria are main issues faced by subjects on SGLT2 inhibitors during Ramadan. There are safety concerns of worsening renal functions especially when subjects cannot counteract polyuria due to fasting. Physicians should exercise caution when SGLT2 inhibitor is prescribed with a diuretic as it potentiates dehydration. Frequent checking of renal function during Ramadan is also advised.